Strategies to target SARS-CoV-2 entry and infection using dual mechanisms of inhibition by acidification inhibitors. - Chaitra Prabhakara; Rashmi Godbole; Parijat Sil; Sowmya Jahnavi; Shah-E-Jahan Gulzar; Thomas S van Zanten; Dhruv Sheth; Neeraja Subhash; Anchal Chandra; Akshatha Shivaraj; Patricia Panikulam; Ibrahim U; et al. (PLoS Pathogens)
Many viruses utilize the host endo-lysosomal network for infection. Tracing the endocytic itinerary of SARS-CoV-2 can provide insights into viral trafficking and aid in designing new therapeutic strategies. Here, we demonstrate that the receptor binding domain (RBD) of SARS-CoV-2 spike protein is internalized via the pH-dependent CLIC/GEEC (CG) endocytic pathway in human gastric-adenocarcinoma (AGS) cells expressing undetectable levels of ACE2. Ectopic expression of ACE2 (AGS-ACE2) results in RBD traffic via both CG and clathrin-mediated endocytosis. Endosomal acidification inhibitors like BafilomycinA1 and NH4Cl, which inhibit the CG pathway, reduce the uptake of RBD and impede Spike-pseudoviral infection in both AGS and AGS-ACE2 cells. The inhibition by BafilomycinA1 was found to be distinct from Chloroquine which neither affects RBD uptake nor alters endosomal pH, yet attenuates Spike-pseudovirus entry. By screening a subset of FDA-approved inhibitors for functionality similar to BafilomycinA1, we identified Niclosamide as a SARS-CoV-2 entry inhibitor. Further validation using a clinical isolate of SARS-CoV-2 in AGS-ACE2 and Vero cells confirmed its antiviral effect. We propose that Niclosamide, and other drugs which neutralize endosomal pH as well as inhibit the endocytic uptake, could provide broader applicability in subverting infection of viruses entering host cells via a pH-dependent endocytic pathway.